Penggunaan Metode Blackbox pada Rancangan Sistem Informasi Pemesanan Produk Tirai Berbasis WEB - Fiyan Firmawan; Rouli Doharma MS (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
The Information System is a collection of systems in its aspect consisting of software, hardware and brainware in a structured manner with performance in a gradual and interconnected process so as to create a specific product that is needed by the user, but related to ordering curtain products for customers in companies generally have a process of ordering curtain products to customers from the company, but along with the development of a website-based information system that can make it easier for companies to carry out performance in the process of ordering curtain products for customers, then from ordering curtain products to customers there are several problem factors that influence it, namely, the difficulty of ordering products curtains because they still use paper for recording so that it takes quite a long time and customers cannot know the availability of curtain products to re-stock again, the purpose of which is a reference for research is to design an information system for ordering curtain products for customers so that they can be fast and flexible, Based on these 2 problems, the solution is to create an information system according to the needs of ordering curtain products that will be used by the company in serving the ordering process, then from this it will create the results of an information system for ordering curtain products for companies for website-based customers, before being used by users from development that makes the application perform testing with blackbox as an evaluation stage of the information system that has been made based on features, blackbox has concepts such as verifying the features used if appropriate will obtain valid results whereas if not appropriate then retesting the information system.